CLASSROOM INTERACTION AS A PREDICTOR OF THE EFFECTIVENESS OF HISTORY EDUCATIONAL TRIPS - Zhu , Meilan; Razak, Ateerah Abdul; Jamalludin, Nur Hafifah (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study examines the effectiveness of classroom interactions and history educational trips. Drawing on existing research, three hypotheses were developed for the study. The results of the study, obtained through quantitative analysis, corroborate and add to previous findings, suggesting that such interactions facilitate effective learning environments and student learning on history trips. The study also provides recommendations for teachers and administrators.